Improving Urgency of Providing First Aid by Providing First Aid Kit in Selected Classroom in Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The researchers chose this topic because everyone inside the classroom should have an awareness of how to take of their health to lessen the number ofstudents being sick every day. The importance of our topic is for the students that far from the clinic to get their medicine immediately. The purpose of this study is to help students who are sick by using a medicine kit inside their classrooms in the Accountancy, Business, and Management Strand. To provide their first aid kit, and to protect them from a severe illness. This study used the survey method to gather the needed information. The sample size was 50 out of 900 Grade 12 Accountancy, Business, and Management (ABM)Strand students in Bestlink College of the Philippines. The study was nonprobability because the sample was chosen randomly from Grade 12 ABM students. The respondents were selected through convenience sampling to allow the students to answer comfortably without hesitation; this way, their answers will be true and honest. The result of the study showed that having a first aid kit in selected classrooms improved the knowledge of the students and teachers in performing first aid medication. Providing first aid kits improved the immediate and right action for emergencies or disasters. This result showed that first aid kits should be provided in classrooms. Based on the summary of findings, the following recommendations were made by the researchers on how Grade 12 ABM students should apply for the basic first aid assistance in terms of (1) emergencies by providing first aid kit to give immediate care to heal common sickness, (2) minor accidents by conducting orientations and seminars on how to perform basic first aid assistance to give the student enough knowledge to apply it to real life, and (3) disasters by providing training on disaster action to lessen the number of casualties.
Keywords: urgency, first aid, emergencies, minor accidents, disaster